CPjBL Versus PjBL Instruction: The Practice of Reviewing Literature From Reputable Journals - Muzaini, Muhammad; Rahayuningsih, Sri; Akib, Irwan; Kamaruddin, Rahmat (Indonesia Approach Education, 2024)
The present study compared the quality of student projects in reviewing literature from reputable journals using computer-assisted project-based learning (CPjBL) and traditional project-based learning (PjBL). This experimental study involved students from a research methodology course at a private university. Experimental group one implemented CPjBL, and experimental group two applied PjBL. The analysis results showed a mean score of 76.41, a standard deviation value of 9.105 for CPjBL, a mean score of 69.78, and a standard deviation value of 9.983 for PjBL. These results suggest that while the mean score of CPjBL was higher than that of PjBL, the difference was insignificant. In conclusion, in a research methodology course, CPjBL is suitable for helping students generate research ideas by optimizing software to review literature from reputable journals.